SOCIAL CONFLICT IN RIAN JOHNSON’S MOVIE SCRIPT KNIVES OUT - Sonie Moezakir Lubis; Andang Suhendi (Universitas Islam Sumatera Utara, 2023)
This study deals with an analysis of the protagonist’s social conflict in the Knives Out movie script written by Rian Johnson (2019). This study found out the kinds of social conflict, like human-to-human and human-to-society conflict, and the ways protagonists faced the social conflict. The theory of conflict used in this study was the theory of conflict proposed by Soekanto (2012). This study used the descriptive qualitative method proposed by Cohen because the process of the result and also the discussion were accomplished descriptively. The method applied was descriptive. It was to describe the kinds of social conflict and the way the protagonist faced the social conflict through the quotation in the movie script. The result of this study was that the protagonist faced social conflict to get the inheritance, even though it was not from the real family. The conflict occurs between humans and between humans and society.